Values of Betawi Ethnic Local Wisdom as a Source of Geographic Teaching Materials - Tawakal, Pref Bambang; Maryani, Enok; Nandi, Nandi (International Conference on Elementary Education, 2020)
Betawi Ethnic local wisdom is the value of knowledge gained in response to the natural challenges faced. The Jakarta area is actually a fertile region and is very suitable for agriculture, so that the values of Betawi Ethnic local wisdom cannot be separated from the natural picture of the mind around agriculture which has undergone many changes. Understanding the values of local wisdom in interacting with daily life is believed by many parties to be able to keep the atmosphere of disharmony towards an atmosphere of harmony amid an increasingly complex circle of diversity. Local wisdom as a form of Betawi ethnic intelligence can be a guide to high-value social life in the current era of globalization. The local wisdom values of Betawi Ethnic can be integrated in learning, as one of the teaching materials in the effort to form and strengthen the nation's character based on local culture